Parent-Child Information Frictions and Human Capital Investment: Evidence from a Field Experiment - Peter Leopold S. Bergman (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper uses a field experiment to answer how information frictions between parents and their children affect investments in education and how much reducing these frictions can improve student achievement. In Los Angeles, a random sample of parents was provided de-tailed information about their child's academic progress. I frame the results in the context of a persuasion game between parents and their children. Parents have upwardly-biased beliefs about their child's effort and the information treatment reduces this bias while increasing parental monitoring. More information allows parents to induce more effort from their children, which translates into significant gains in achievement. Relative to other interventions, additional information to parents potentially produces gains in achievement at a low cost.
Keywords: I20; I21; I24; 330; information frictions; experiment; parents